2017
DOI: 10.3389/fphys.2017.00171
|View full text |Cite
|
Sign up to set email alerts
|

Effects of 12 Weeks Resistance Training on Serum Irisin in Older Male Adults

Abstract: Background: To assess the effects of resistance training on circulating irisin concentration in older male adults, and to investigate the association between resistance training induced alteration of irisin and body fat.Methods: Seventeen older adults (mean age is 62.1 years old) were randomized into old control group (male, n = 7), and old training group (male, n = 10). The control group has no any exercise intervention. The resistance training group underwent leg muscle strength and core strength training pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
55
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(60 citation statements)
references
References 23 publications
(37 reference statements)
2
55
0
1
Order By: Relevance
“…Irisin is an exercise-induced adipomyokine and circulating irisin levels are significantly elevated after both acute and chronic exercise [6,[47][48][49]. Moreover, it has been reported that exercise-stimulated release of irisin is independent of age or fitness level [49], although there are differences in the basal circulating irisin levels [48,49].…”
Section: Discussionmentioning
confidence: 99%
“…Irisin is an exercise-induced adipomyokine and circulating irisin levels are significantly elevated after both acute and chronic exercise [6,[47][48][49]. Moreover, it has been reported that exercise-stimulated release of irisin is independent of age or fitness level [49], although there are differences in the basal circulating irisin levels [48,49].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, studies in aging mice and humans revealed that circulating irisin significantly increased following RET (Kim et al, 2015;Zhao et al, 2017). It seems that differences in the participants' age range can be considered as a reason for the differences in results.…”
Section: Discussionmentioning
confidence: 99%
“…While a large body of literature exists regarding the effects of chronic exercise training on irisin in adults, the results of many studies have been far from conclusive, and no consensus has been reached. Some studies have shown the potential effects of exercise training on circulating irisin (Boström et al, 2012;Ercan et al, 2017;Ghanbari-Niaki et al, 2018;Kim, So, Choi, Kang, & Song, 2015;Moienneia & Hosseini, 2016;Zhao, Su, Qu, & Dong, 2017) and myostatin (Hinkley, Konopka, Suer, & Harber, 2017;Hittel et al, 2010;Roth et al, 2003;Saremi et al, 2010;Walker, Kambadur, Sharma, & Smith, 2004). While others have shown that irisin (Ellefsen et al, 2014;Hecksteden et al, 2013;Moienneia & Hosseini, 2016;Pekkala et al, 2013) and myostatin (Besse-Patin et al, 2014;Binns, Gray, Henson, & Fort, 2017;Hofmann et al, 2016;Ziaaldini et al, 2015) may not change after long-term exercise training.…”
Section: Introductionmentioning
confidence: 99%
“…However, the studies on the impact of exercises on the recently-discovered irisin are limited and the publications that express that only the acutely performed resistance and aerobic exercises increase the irisin concentration [16,17,18], but the long-term exercise programs do not affect the irisin concentration [19,20,21], and recent studies even reduce irisin [22] are encountered as well. It appears that the studies regarding the responses of irisin to acute and chronic exercises have been conducted in different age groups and in the study design with different exercise type and duration (resistance, aerobic etc), in the healthy females and males with different activity levels [23,24,25], in the patients with diabetes [26] or in obese individuals [27]. It was observed that even though the impacts of training and gender have been researched in the studies about irisin, the subjects were not elite athlete.…”
Section: Introductionmentioning
confidence: 99%